Karaites in the Ulus Jochi era and in the Crimean Khanate: The question of the origin of Karaite communities on the Crimean peninsula - Prokhorov D.A. (Золотоордынское обозрение)
Research objectives: An analysis and generalization of materials on the history of the emergence of Karaite communities on the territory of the Crimean peninsula in the era of the Ulus of Jochi and the Crimean Khanate. Research materials: As a result of comparing published materials on the history of the Crimean Karaites, data from archaeological and epigraphic studies, as well as in the process of studying the funds of the Russian State Historical Archive (RSHA, St. Petersburg) and the State Archive of the Republic of Crimea (SARC, Simferopol), information was analyzed related to the problem of the emergence of Karaite communities on the territory of Crimea in the era of Ulus Jochi and the Crimean Khanate. Results and scientific novelty: Many episodes in the history of the Crimean Karaites still remain outside the field of view of researchers. There is also the problem of interpretation of sources. In particular, this concerns the controversy about the origin of the Crimean Karaites and the time of their appearance on the territory of the Crimean peninsula, a process that had been going on for more than 100 years with the discussion sometimes going beyond scientific argumentation. The stages of the scientific study of the past of the Crimean Karaites are characterized by different levels of intensity, as well as large variety of methods and approaches used. Interest in this problem first arose among representatives of Russian academic circles in the first half of the 19th century. The Russian administration became interested in the history of the Karaites in part because the ideas of the European Enlightenment, which largely determined the policy of the Russian government in a number of key areas, implied the spread of Russian culture and education to the “Asian peoples.” In relation to the Karaites, Krymchaks, and Ashkenazi Jews, the Russian government adopted laws and regulations, in accordance with which the Karaites were able to legislatively strengthen their legal status. The Russian government, however, used restrictive measures by pursuing a discriminatory anti-Jewish policy against the Jewish population. The Karaites managed to get the authorities to recognize them as a community that differed from the Rabbanites while they received various legal and economic preferences. The same time period marked the onset of the large-scale activity of the famous collector of Jewish antiquities, Abraham Firkowicz, who initiated the creation of an extensive collection of manuscripts related to the history of Jewish communities, including in the Crimean peninsula. Based on the materials presented, it was concluded that the Karaite community could have appeared in the Crimea not earlier than the second half of the 13th century. Active resettlement of Karaites to the Crimea from the territories of the Middle East, Byzantium, and subsequently from the Ottoman Empire had been taking place since the middle of the 14th century. These chronological periods are also supported by material evidence of the stay of the Karaites in this region (archaeological and epigraphic studies of medieval Solkhat, Mangup-Kale, and Chufut-Kale).